Generalized linear model for enhancing the temperature measurement performance in Brillouin optical time domain analysis fiber sensor - Nordin N.D.; Zan M.S.D.; Abdullah F. (Academic Press Inc., 2023)
Curve fitting; Deterioration; Fiber optic sensors; Forecasting; Learning algorithms; Machine learning; Signal to noise ratio; Temperature measurement; Temperature sensors; Theorem proving; Brillouin frequency shifts; Brillouin gain spectrum (BGS); Brillouin optical time domain analysis; Distributed temperature sensing; Generalized linear model; Low signal-to-noise ratio; Temperature prediction; Temperature resolution; Time domain analysis